Employee Performance Of Hotel Tampiarto Plaza Probolinggo Influenced By The Dimensions Of Motivation - Hermawan, Dedi Joko (International Journal of Accounting and Management Research, 2024)
The purpose of this study was to determine how the dimensions of motivation affect employee performance at the plaza hotel located in the city of probolinggo both simultaneously and partially. this study uses a quantitative descriptive approach with five variables contained in the dimensions of motivation. the number of samples in this study were 39 employees registered at the Tampiarto plaza probolinggo hotel, the researchers used the entire number of employees using the sampling technique, namely saturated sampling. the data collection method used in this study was a questionnaire measured by a Likert scale and validity and reliability testing. data processing using the SPSS version 22 program as a multiple linear analysis test tool, F test, and T test. the results of the study prove that the dimensions of motivation affect the performance of employees of the tampiarto plaza probolinggo hotel both simultaneously and partially. partially physiological needs affect employee performance, a sense of security affects employee performance, social needs affect employee performance, self-esteem or recognition affects employee performance, and self-actualization affects employee performance. while simultaneously proving that five variables in the dimensions of motivation affect employee performance.